Trinational Study Exploring the Early Impact of the COVID-19 Pandemic on Organ Donation and Liver Transplantation at National and Unit Levels. Issue 11 (November 2020) - Reddy, Mettu S.; Hakeem, Abdul R.; Klair, Tarunjeet; Marcon, Francesca; Mathur, Abhishek; Samstein, Benjamin; Mohanka, Ravi; Mathur, Surendra K.; Prachalias, Andreas; Menon, Krishna V.; Muiesan, Paolo; Rela, Mohamed; et al.
Abstract : Background: The coronavirus disease (COVID-19) pandemic is stressing healthcare services to an unprecedented extent. There is anecdotal evidence of reduction in organ donation and transplantation activity across the world. Methods: The weekly organ donation and liver transplant numbers over a 3-month period (Feb 17, 2020, till May 17, 2020) for the United States, United Kingdom, and India were compared with their previous year's activity. Liver transplant activity in 6 centers from these countries with varying local COVID-19 caseload was also compared. Results: The COVID-19 pandemic has led to a significant contraction in organ donation and liver transplantation in all 3 countries. Peak reduction ranged from 25% in the United States to over 80% in the United Kingdom and India. The reduction was different for deceased donor and living donor liver transplantation and varied between centers within a country. There was early evidence of recovery of deceased donation in the United States and United Kingdom and resumption of living donor liver transplantation activity in India toward the end of the study period. A number of policy changes were undertaken at national and transplant center levels to ensure safe transplantation despite significant redirection of resources to combat the pandemic. Conclusions: There was a substantial reduction in organ donation and liver transplantation activity across the 3 countries with signs of recovery toward the end of the study period. Multiple factors including COVID-19 severity, stress on resources and influence of regulatory agencies and local factors are responsible for the reduction and recovery. Abstract : Supplemental Digital Content is available in the text.